Carbon Content In Macroalgae Species Against Temperature Regime - Tri Dewi Kusumaningrum Pribadi; Yudi Nurul Ihsan (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2019)
Temperature rise due to climate change have an impact on various ecosystems, including coastal ecosystems. Temperature rise also affects plant metabolism, such as carbon uptake. Macroalgae is the dominant community in the intertidal zone, and potential to absorb carbon. A series of experiments on several dominant macroalgae species from the south coast of West Java have been done to see the effect of temperature regime on carbon content. The treatment of temperatures of 24, 27, 30, and 33 °C was carried out for 72 hours against 6 macroalgae species representing Chlorophycae, Phaeophycea and Rhodophyceae to investigate carbon content. The results showed that the macroalgae of Phaeophyceae division showed higher carbon content in comparison to the macroalgae of the other divisions. The temperature that significantly affects chloropyll was 33 oC against all the species being tested.